2008
DOI: 10.1074/mcp.m700524-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Molecular Complexity of Phosphorylated Human Cardiac Troponin I by Top Down Electron Capture Dissociation/Electron Transfer Dissociation Mass Spectrometry

Abstract: Cardiac troponin I (cTnI), the inhibitory subunit of the thin filament troponin-tropomyosin regulatory complex, is required for heart muscle relaxation during the cardiac cycle. Expressed only in cardiac muscle, cTnI is widely used in the clinic as a serum biomarker of cardiac injury. In vivo function of cTnI is influenced by phosphorylation and proteolysis; therefore analysis of post-translational modifications of the intact protein should greatly facilitate the understanding of cardiac regulatory mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
164
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(179 citation statements)
references
References 66 publications
13
164
2
Order By: Relevance
“…However, we previously found that Ser22 is the predominant site that is basally phosphorylated in monophosphorylated cTnI from rat hearts, 32 consistent with a previous MS/MS analysis of human cTnI. 39 Fragmentation of bisphosphorylated cTnI (2P) from samples treated with inactive AMPK localized the phosphorylation to Ser22 and Ser23 (the PKA sites), as c 20 and c 21 ions were only detected as unphosphorylated, c 22 was detected as monophosphorylated, and c 23 and all c ions beyond c 23 were detected as bisphosphorylated. Importantly, for both mono-and bisphosphorylated cTnI forms treated with inactive AMPK, all z ions were unphosphorylated, ruling out the potential basal phosphorylation of Ser149 [ Fig.…”
Section: Incorporation Of 32 P Into Recombinant Ctni By Ampksupporting
confidence: 89%
See 1 more Smart Citation
“…However, we previously found that Ser22 is the predominant site that is basally phosphorylated in monophosphorylated cTnI from rat hearts, 32 consistent with a previous MS/MS analysis of human cTnI. 39 Fragmentation of bisphosphorylated cTnI (2P) from samples treated with inactive AMPK localized the phosphorylation to Ser22 and Ser23 (the PKA sites), as c 20 and c 21 ions were only detected as unphosphorylated, c 22 was detected as monophosphorylated, and c 23 and all c ions beyond c 23 were detected as bisphosphorylated. Importantly, for both mono-and bisphosphorylated cTnI forms treated with inactive AMPK, all z ions were unphosphorylated, ruling out the potential basal phosphorylation of Ser149 [ Fig.…”
Section: Incorporation Of 32 P Into Recombinant Ctni By Ampksupporting
confidence: 89%
“…ECD has been demonstrated to be especially valuable for mapping phosphorylation sites, because it preserves the labile PTMs during MS/MS process. [32][33][34]39,40 To obtain a complete view of the phosphorylation state of whole cardiac troponin (cTn) complexes that have been treated with AMPK, purified whole Tn complexes from a single rat heart were analyzed by high-resolution top-down MS. 32 This approach, combined with the use of synthetic peptides, sitedirected mutagenesis, and phosphospecific antibodies, and identified Ser149 and Ser22 as the only sites targeted by AMPK, with Ser149 as the preferred site. AMPK was found to phosphorylate cTnI at the level of cTnI peptides, the intact cTnI subunit, whole cTn complexes and skinned cardiomyocytes, indicating that cTnI is a substrate for AMPK even when assembled with other contractile proteins in highly ordered myofilaments.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the conventional ''bottom-up'' MS approach where proteins of interest are digested with an enzyme before MS analysis providing only partial coverage of the protein sequence with loss of connectivity between modified peptides from disparate regions of the protein (23,27,28), a ''top-down'' MS approach is extremely attractive for characterization of complex PTMs in proteins of 10 to 200 kDa (22,25,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). The top-down MS approach directly analyzes intact protein, allowing simultaneous observation and quantification of all possible protein modifications, and subsequently fragments the protein ions of interest in the mass spectrometer to locate the modification site(s) with full sequence coverage (25,29,30,36). Moreover, the top-down MS approach is especially attractive for quantitatively determining the relative abundance of protein species with specific modifications, since the ionization efficiency of intact proteins is much less affected by the presence of modifying groups in comparison with peptides (22,25,35).…”
mentioning
confidence: 99%
“…Biomolecular mass spectrometry (MS) (21) is the only technique that can universally provide information about protein posttranslational modifications (PTMs) without a priori knowledge (22)(23)(24)(25)(26). In contrast to the conventional ''bottom-up'' MS approach where proteins of interest are digested with an enzyme before MS analysis providing only partial coverage of the protein sequence with loss of connectivity between modified peptides from disparate regions of the protein (23,27,28), a ''top-down'' MS approach is extremely attractive for characterization of complex PTMs in proteins of 10 to 200 kDa (22,25,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…It has been generally accepted that phosphorylation of these sites is an important mechanism for increasing the rate of relaxation during β-adrenergic receptor stimulation in the heart. Also, cross-phosphorylation of Ser23/24 by PKC, PKG, or PKD, even though less efficient than that of PKA, has a similar effect on the sensitivity of the myofilaments to calcium, indicating a beneficial role of phosphorylation of these sites for the relaxation rate of the heart Effects of troponin I phosphorylation: transgenic animal studies PKC is able to phosphorylate cTnI at Ser23/24, Ser43/45, Thr143, and Ser76 (or Thr77) (Fig.1, Table 1) Noland et al 1989;Swiderek et al 1990;Zabrouskov et al 2008). Sakthivel et al (2005) studied the effects of cTnI phosphorylation by PKA and PKC using transgenic mice models in which either all five phosphorylation sites on cTnI (Ser23/24, Ser43/45, and Thr143) were changed into aspartic acid to mimic complete phosphorylation, or only the PKA sites (Ser23/24).…”
Section: Thin Filament Regulationmentioning
confidence: 99%